Cost of hospital services in India: a multi-site study to inform provider payment rates and Health Technology Assessment - Akashdeep Singh Chauhan; Lorna Guinness; Pankaj Bahuguna; Maninder Pal Singh; Vipul Aggarwal; Kavitha Rajsekhar; Surbhi Tripathi; Shankar Prinja (BMC Health Services Research, 2022)
The 'Cost of Health Services in India (CHSI)' is the first large scale multi-site facility costing study to incorporate evidence from a national sample of both private and public sectors at different levels of the health system in India. This paper provides an overview of the extent of heterogeneity in costs caused by various supply-side factors.
Keywords: Costing; Hospitals; Private providers; Prices; India